Kepatuhan dan Kualitas Hidup Pasien Diabetes Melitus Tipe 2 di Rumah Sakit di Jawa Tengah - Mutmainah, Nurul; Al Ayubi, Muhammad; Widagdo, Anggie (Universitas Muhammadiyah Surakarta, 2020)
Diabetes mellitus is a chronic disease that requires treatment for a long period of time. Adherence to consuming drugs is one of the most important things in achieving treatment goals. This study aims to determine the level of adherence and quality of life and determine the relationship to the quality of life of patients with type 2 DM in hospitals in Central Java. This study uses analytic design by asking cross-sectional. Samples were taken at two hospitals in Central Java. Sampling was purposive sampling with the criteria of type 2 diabetes mellitus patients who are undergoing outpatient care in the hospital, have undergone therapy for at least 3 months, and can communicate well. As a measurement used the Medication Adherence Rating Scale (MARS) questionnaire while the quality of life measure used the Short Form 36 (SF-36) questionnaire. Score data received and quality of life that has been obtained was processed with the SPSS (Product Statistics and Service Solutions) chi-square test. Research results in 200 respondents found 9 people (4.5%) had low adherence, 46 people (23%) were moderately related and 145 people (72.5%) have high adherence. While the quality of life found 41 people (20.5%) had a poor quality of life and 159 people (79.5%) had a good quality of life. The lowest aspect of quality of life is physical limitations and the highest aspect of quality of life is mental health. From the results of the analysis on the chi square test, the p value was obtained: 0.00. This shows that there is a significant relationship between adherence and quality of life in patients with Type 2 diabetes mellitus at the hospitals and a Prevalence Ratio value of 23.47.